Central adiposity as a predictor of mortality in older adults: Identification of cutoffs using generalized additive models - Fernandes, Dalila Pinto de Souza; Lopes Juvanhol, Leidjaira; Nobre, Aline Araújo; de Souza, Ângela Maria Natal; Ribeiro, Andréia Queiroz (Frontiers in Nutrition, 2023)
Background: The oObesity is associated with premature mortality in adults;, buthowever, this association has been inconsistent in the older adults population. Besides that, have the absencethere is a lack of specific cutoff points for indicators to predictof negative health outcomes for thein older adults. Methods: Prospective study with 796 non-institutionalized older adults, non-institutionalized. At the baseline, Data on sociodemographic characteristicsinformation, lifestyle, food consumption and nutritional status were obtained at baseline. Generalized additive models were used to identify cut-off points for waist circumference (WC) and waist-to-height ratio (WHtR) and Cox proportional hazards models to assess the independent association between adiposity and mortality. Results: Over the 9 years of follow-up There were 197 deaths (24.7%) occurred,in the follow-up period of which 51.8%were men, with mean age of 76.1±9.0 years. Older adults at higher risk of death had WHtR < 0.52 or ≥ 0.63 and WC < 83 cm or ≥ 101 cm (for both sexes). An increased risk of death was observed in the older adults with high WC (HR: 2.03 95% CI: 1.20-3.41) and with high WHtR (HR: 1.51 95% CI: 1.01-2.26) in the adjusted models as well an increase in WC was a risk factor for higher CVD mortality (HR: 2.09, 95% CI: 1.12-3.88) in the adjusted. Conclusions: Adiposity was associated with an increased risk of death in older adults. In view of these results and considering the lack of cutoff points for anthropometric indices in Brazilian older adults population, subsequent furtherstudies are needed to confirm may confirm our the WC and WHtR cutoff points values found in this study for Brazilian older adults.